2019
DOI: 10.20546/ijcmas.2019.807.183
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Ameliorates the Mineralo-Oxidative Stress of Sucking Lice Infestation in Indian Water Buffalo

Abstract: Buffaloes considered as -black gold of India‖; because buffaloes provide high quality protein, fat rich milk, serve as a source of employment and livelihoods to millions of landless, marginal, and small farmers (Syed Mohmad and Manmohan Singh, 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Dimri and Sharma (2004) had reported that, Vitamin C supplementation along with miticidal therapy recovered the sarcoptic mange infestation in sheep. Vitamin C administration had the ability to suppress Th2 immune response by increasing the interferon gamma with simultaneous reduction of IL-4, reduced serum histamine and IgE levels (Sun et al, 2009) and Ajith et al, (2019) also had reported the similar result with Vitamin C supplementation in caprine pediculosis. N-Acetyl cysteine (NAC), a mucolytic agent with antioxidant properties, has been successfully used in human patients for several years to treat acute and chronic bronchitis, and had been used as effective antidote for paracetamol toxicity.…”
Section: Table1 Mean Lice Count In Different Body Regions Of Sucking Lice (Haematopinus Tuberculatus)mentioning
confidence: 71%
See 2 more Smart Citations
“…Dimri and Sharma (2004) had reported that, Vitamin C supplementation along with miticidal therapy recovered the sarcoptic mange infestation in sheep. Vitamin C administration had the ability to suppress Th2 immune response by increasing the interferon gamma with simultaneous reduction of IL-4, reduced serum histamine and IgE levels (Sun et al, 2009) and Ajith et al, (2019) also had reported the similar result with Vitamin C supplementation in caprine pediculosis. N-Acetyl cysteine (NAC), a mucolytic agent with antioxidant properties, has been successfully used in human patients for several years to treat acute and chronic bronchitis, and had been used as effective antidote for paracetamol toxicity.…”
Section: Table1 Mean Lice Count In Different Body Regions Of Sucking Lice (Haematopinus Tuberculatus)mentioning
confidence: 71%
“…Anemia in bubaline pediculosis might be a consequence of prolonged blood loss, iron deficiency mediated by oxidative stress, loss of vital nutrients, oxidative stress induced RBC damage (Madhesh et al, 2019;Yoo et al, 2009). In conclusion, bubaline pediculosis caused by sucking lice is associated with severe oxidative stress, and haematological changes such as anemia, leukocytosis with neutrophilia, lymphocytopenia, and eosinophilia.…”
Section: Table1 Mean Lice Count In Different Body Regions Of Sucking Lice (Haematopinus Tuberculatus)mentioning
confidence: 87%
See 1 more Smart Citation
“…[44,18]. Previous studies suggested that external parasite infestation could cause iron-deficiency anemia, which lowers hemoglobin levels and other red blood cell components in both people and animals [45,46,47,18]. Due to rivalry between the sponsor and the host for the blood's food source, hemoglobin levels may have decreased.…”
Section: Discussionmentioning
confidence: 99%